Continuous meteorological observations at station Ny-Ålesund (2024-07) - Marion Maturilli (PANGAEA, 2024)
The meteorological observatory Neumayer continuously acquires meteorological parameters. Measurements are taken on or near the meteorological 10m-mast, located some 300m south-east of the main station building. Co-located there are BSRN (Baseline Surface Radiation Network) measurements taken. The measurement interval of the raw data is approximately 6s. Data is quality controlled: All measurements are checked daily on site and again prior to publication according to BSRN standards. Knowingly affected or erroneous data is removed.
In: Maturilli, M (2020): Continuous meteorological observations at station Ny-Ålesund (2011-08 et seq) [dataset publication series]. Alfred Wegener Institute - Research Unit Potsdam, PANGAEA, https://doi.org/10.1594/PANGAEA.914979